2016
DOI: 10.1080/17452007.2016.1187111
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the design–construction interface problems in the UAE

Abstract: Design-construction interface problems impede the successful delivery of construction projects within the specified time, cost and quality. The objective of this paper is to assess the design-construction interface problems in the United Arab Emirates (UAE) construction industry. Twenty-two problems were identified through literature review. A questionnaire survey was then developed and distributed to construction professionals. Thirty-nine responses were collected from consultants, contractors and constructio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Interface problems that could exist during either the design phase, construction phase, or during both (i.e., design-construction interface) can be found in the past literature [62][63][64][65]. Many items on the list that contain design-construction interface problems are extracted from different papers.…”
Section: Common Interface Problems In Construction Projectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interface problems that could exist during either the design phase, construction phase, or during both (i.e., design-construction interface) can be found in the past literature [62][63][64][65]. Many items on the list that contain design-construction interface problems are extracted from different papers.…”
Section: Common Interface Problems In Construction Projectsmentioning
confidence: 99%
“…Al Mousli and El-Sayegeh (2016) defined a list of 22 design-construction interface problems and conducted a survey among construction professionals in the UAE. Survey results showed that the main design-construction interface problems were related with the lack of coordination and management throughout the project life cycle [64].…”
Section: Common Interface Problems In Construction Projectsmentioning
confidence: 99%
“…An integrated implementation relies on close communications between project participants [15][16][17][18]. With the occurrence of CIM (computer integrated manufacturing) propagation and applications of IT into construction activities [19], the essence of integration has experienced a thorough variation over the past few years [20,21].…”
Section: Integration On Construction Projectsmentioning
confidence: 99%
“…e findings present in the literature work in this category suggest that the redefining work roles [9,85] and designing relationships [30] have been considered as positive factors to support organizational integration. In addition, some scholars have proposed that establishing the mechanism of benefit conforming and contradiction handling contribute to can effectively improve the level of trust and then promote the cooperation of participants [17,59,61].…”
Section: Organization Dimension Of Integration In Bbcnsmentioning
confidence: 99%
“…The high uncertainty nature of preliminary design in hydropower EPC projects implies that integrating design with procurement and construction is critical over the course of project delivery [61][62][63]. As design governs procurement and construction activities, coordinating various design departments to meet requirements of project schedule is also a key aspect of design-related interface management [61,64].…”
Section: Design Managementmentioning
confidence: 99%